MANAJEMEN PENGGUNAAN BANTUAN OPERASIONAL SEKOLAH (BOS) SD NEGERI 015 DESA PASIR KERANJI KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Rinanda, Rifki; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Help Operational School(BOS) is a government program that is basically for supplying of funding the operating costs of the non personalia for the basic education units implementing as compulsory. According to PP number 48 in 2008 about funding education, the cost of non personalia is costs for materials of equipment consumables and indirect costs in the form of recources, water, telecommunication services, maintenance of facilities and infrastructure, overtime money, transportation, consumption, taxes etc. Fund of BOS based on Regulation directive generally BOS program, in general aim to relieve of the community against the financing of education in the frame work of compulsory 9 years of quality.The concept theory of researcher use is a theory of management for analyzing the implementation process management of the of the funds of BOS that is theory G.R Terry. The Method used in this research is Kualitatif Deskriptif method with instrument Data collection techniques include from interview, observation, the study of librarianship and document program BOS that relevant with the goals of research.This results of this study demonstrate of the funds management BOS at primary school level. Especially Primary School 015 Pasir Keranji is not optimal yet. The planning stages haven’t yet to accomodate the student needs because the low community participation in meetings and the preparation of Planning Activity Cost of School(RKAS). The process of organizing there is division of tasks clear yet. While the process of the implementation funds of BOS , there is is still transferred their used or appropriate RKAS with Administrative supervision or report of accounting funding BOS.Key Words: BOS program, Management, Education, RKAS